New Research on MEMS Acoustic Vector Sensor Used in ground Marker of Pipeline - Mengran Liu; Guojun Zhang; Zeming Jian; Hong Liu; Xiaopeng Song; Wendong Zhang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Recently, ground marker based on the principle of acoustic detection has become the trend of pipeline technology. As to the difficulty and low accuracy of ground marker, this paper introduces a new MEMS bionic acoustic vector sensor with high sensitivity, good performance in low frequency and lower power. As to the problem of the port/starboard blur of this vector sensor in ground marking, it proposes a new plan and proves the correctness of the plan through theoretic analysis and experimental verification. The results show that the mean error of the directional angle is within 5 degree meeting the needs of the engineering project.